Perception of consanguineous marriage among the qatari population - Yasamin Abdu; Khalid Ahmed; Mohamed Izham Mohamed Ibrahim; Mariam Abdou; Arwa Ali; Hind Alsiddig; Nagah A. Selim; Mohammed A. Yassin (Frontiers in Public Health, 2023)
BackgroundHereditary blood diseases are widespread among the Arab population due to the high rates of consanguineous marriages; research regarding the perception of consanguineous marriage in some countries, such as Qatar, is extremely scarce. Therefore, this study aimed to investigate the prevalence of consanguineous marriage and assess the perception of consanguineous marriage among the Qatari population.MethodsA cross-sectional study used a self-administered questionnaire among 395 Qatari adults aged 18–35 who attended primary healthcare institutions in Qatar. A convenience sampling technique was used to select the study participants. An independent t-test was used to compare the significance of the mean between the two groups with positive and negative perceptions of consanguineous marriage. Categorical data were analyzed for association using the chi-square or Fisher's exact test. Finally, a multiple logistic regression analysis was conducted to determine the significant predictors of the positive perception of consanguineous marriage. A significant level was set at p < 0.05.ResultsApproximately 45% of the participants had a positive perception toward consanguineous marriage, and the most common reason stated by those participants was “habit and traditions.” The prevalence of consanguineous marriage among married couples was 62.6%, and among those with consanguineous marriage, most were married to first cousins (81.7%). Moreover, compared to the participants with negative perceptions of consanguineous marriage, those with positive ones were significantly older, married, with lower educational levels and higher monthly income levels, did not hear about glucose-6-phosphate dehydrogenase (G6PD) deficiency, did not know what kinds of diseases are being screened in the premarital test, and were married to a relative.ConclusionThe prevalence of consanguineous marriage is high among the Qatari population, and this requires an immediate need for community-based campaigns to raise public awareness about the problem and its potential impact.